The Influence Of Motive, Personality And Self-Efficacy On Interest In Entrepreneurship Among Smes In Bengkulu City - Yeni Herlina; Ahmad Soleh; Muhammad Rahman Febliansa (Utan Kayu Publishing, 2024)
This research aims to determine the influence of: 1) Motives on interest in entrepreneurship. 2) Personality towards Entrepreneurial Interest. 3) Self-efficacy towards Entrepreneurial Interest. 4) Motives, Personality and Self-Efficacy together on Entrepreneurial Interest. The population in this research is MSME business actors in Bengkulu City. The sample for this research is 100. The questionnaire was tested for validity and reliability before collecting research data. The hypothesis was tested using Multiple Linear regression analysis. This research uses quantitative methods. The data collection tool used a questionnaire which was distributed to the 100 respondents studied, namely MSMEs in the city of Bengkulu. The sampling method in this research, namely non-probability sampling, that will be used is purposive sampling, where sampling in this case is limited to certain types of people who can provide the desired information. The analytical method used in this research is multiple linear regression analysis with data processing using SPSS 23 for Windows. The results of the analysis show that the variables studied have a significant and positive influence. The motive variable has a significant and negative effect on the interest in entrepreneurship of MSME actors in the city of Bengkulu, the personality variable has a significant and positive effect on the interest in entrepreneurship of MSMEs in the city of Bengkulu, the self-efficacy variable has a significant and positive effect on the interest in entrepreneurship of MSME actors in the city of Bengkulu, the variable motive, personality and efficacy Together, they have a significant and positive influence on the entrepreneurial interest of MSME actors in the city of Bengkulu. Interest in entrepreneurship can be explained by the variables motive, personality and self-efficacy by 61% and the remaining 39% is explained by variables outside the model.